Evaluation of Acoustic Radiation Force Impulse Imaging (ARFI) for the Determination of Liver Stiffness Using Transient Elastography as a Reference in Children - Sagir, A.; Ney, D.; Oh, J.; Pandey, S.; Kircheis, G.; Mayatepek, E.; Häussinger, D. (Ultrasound International Open, 2015)
Purpose: Transient elastography (Fibroscan©; (FS)) and acoustic radiation force impulse imaging (ARFI) represent noninvasive, user-friendly and quick methods providing an objective and reproducible measure of liver stiffness. The aim of the study was to evaluate cut-off values and performance of ARFI measurements in children using transient elastography as a reference.Methods/Patients: A total of 198 children were enrolled in this study. All patients underwent liver stiffness measurements with FS (FS-LS) as well as ARFI (with shear wave velocity quantification; ARFI-SWV) and the performance of ARFI in comparison to FS was studied.Results: Significantly higher rates of successful measurements were found for ARFI compared to FS (198/198 (100%) vs. 160/198 (80.8%); p<0.001). ARFI-SWV correlated significantly with FS-LS (r=0.751, p=0.001). ARFI-SWV increased significantly with the stage of fibrosis (1.19+0.15 m/s for patients with FS-LS<7.6 kPa); 1.34+0.22 m/s for patients with 7.6<FS-LS<13.0 kPa); and 1.83+0.58 m/s for patients with FS-LS>13.0 kPa). ARFI-SWV cut-off values were identified for no significant fibrosis (1.31 m/s; sensitivity 61.8% and specificity 79.5%) and for liver cirrhosis (1.63 m/s; sensitivity 70.0% and specificity 97.4%). The median values of liver stiffness measured by FS were age-dependent in 90 children without liver diseases with 4.8, 5.6, and 5.7 kPa in children 0–5, 6–11, and 12–18 years, respectively.
Keywords: abdomen; diagnostic radiology; safety